Analisis Tindak Tutur Guru dan Siswa Dalam Pembelajaran Bahasa Indonesia - Intan Munawarah; Hufratul Jannah; Meri Yulizar; Abdul Haliq (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The purposes of this study are: 1) to describe the speech behavior of teachers and students in learning Indonesian at MTSS Asaasunnajaah Aceh Besar, and 2) to describe The function of speech behavior of teachers and students in learning Indonesian at MTSS Asaasunnajaah Aceh Besar. The sample of this study is the teacher who taught Indonesian and the VI,VII, and IX grade students of MTSS Asaasunnajah Aceh Besar. The method used in this study is a qualitative descriptive research method. The data in this study are the speeches of teachers and students when interacting in classroom. The data source of this study are Indonesian teachers of MTSS Asaasunnajaah Aceh Besar and students in grades VI,VII and IX. The data collection technique used in this study are observation, notion and recording. The data collection techniques in this study are the technique of transcription, data selection, data presentation and conclusion drawing. Based on the data analysis, command voice operations are more widely used than other forms of voice operations. From the research results, it can be seen that the form of command voice action and the function of command voice action used by Indonesian teachers are the form of voice action command 10, request 5, invitation 3, suggestion 5, criticism 4 and prohibition 3. The functions of verbal actions encountered include: command 10, suggest 5, invite 3, prohibit 4, criticize 4 and inquiry 4